Implementasi Wireless Sensor Network untuk Monitoring Limbah Cair Gondorukem Menggunakan Modul Wifi Esp8266 - Risqi Nur Ifansyah; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Indonesia is a country that is rich in natural resources, there are many pine trees that produce sap. Pine tree sap has many uses in the cosmetic, antiseptic and pharmaceutical industries. But pine sap produces a waste effect. There are still many things that need to be improved on the processing of gondorukem for wastewater treatment. Especially in the disposal section, it is not possible to predict a good standard of liquid waste disposal. The standard for wastewater disposal has several parameters such as pH, temperature and turbidity of the waste. With IoT technology, it makes it easier for us to reduce the pH, temperature and turbidity of the waste by using a pH meter water sensor, DS18B20 and Turbidity. The data of the three sensors are collected to the sensor node, then sent to the gateway via a websocket, then forwarded to firebase which will be displayed on the web interface. Testing uses Quality of Service, to determine a network speed performance when sending, which is useful for knowing the time of each delivery and packets lost during delivery. The water meter's pH sensor function, DS18B20 and Turbidity, worked well during research. Then obtained from the test results based on the throughput h-1 to h-4 testing is 17.01 bps, 20.89 bps, 19.83 bps and 18.86 bps. For packet loss h-1 to h-4, namely 0.1%, 0%, 0% and 0.%. Then the delay h-1 to h-4 is 0.08 s, 0.07 s, 0.07 s, and 0.07 s.